Sosialisasi Manfaat Pengemasan Untuk Meningkatkan Daya Saing Produk UMKM Snack Pak Muklis - Putra, Iswidana Utama; Nafturahma, Nadya Al (Jurnal Dehasen Mengabdi, 2023)
Micro, Small and Medium Enterprises (MSMEs) are productive businesses owned by individuals or business entities that have met the criteria as micro businesses. One of them is Mr. Muklis's Snack business in Talang Saling village. Based on the results of a survey conducted at Mr. Muklis' business, it is known that his business is still not prominent in the midst of increasingly fierce competition. This is because the product packaging still uses ordinary and unattractive packaging, as well as the lack of knowledge about the benefits of packaging for a product. Based on these problems, we aim to help business owners by socializing the benefits of packaging for a product to increase competitiveness